Can psychosocial risk factors mediate the association between precarious employment and mental health problems in Sweden? Results from a register-based study - Méndez-Rivero, Fabrizio; Matilla-Santander, Nuria; Gunn, Virginia; Wegman, David H.; Hernando-Rodriguez, Julio C.; Kvart, Signild; Julià, Mireia; Kreshpaj, Bertina; Bodin, Theo; Hemmingsson, Tomas; Muntaner, Carles; Padrosa, Eva; et al. (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'The aim of this study was to examine the mediating effect of the psychosocial work environment on the association between precarious employment (PE) and increased risk of common mental disorders (CMD), substance use disorders and suicide attempts. ' ' METHODS ': 'This longitudinal register-study was based on the working population of Sweden, aged 25–60 years in 2005 (N=2 552 589). Mediation analyses based on a decomposition of counterfactual effects were used to estimate the indirect effect of psychosocial risk factors (PRF) (mediators, measured in 2005) on the association between PE (exposure, measured in 2005) and the first diagnosis of CMD, substance use disorders, and suicide attempts occurring over 2006–2017. ' ' RESULTS ': 'The decomposition of effects showed that the indirect effect of the PRF is practically null for the three outcomes considered, among both sexes. PE increased the odds of being diagnosed with CMD, substance use disorders, and suicide attempts, among both men and women. After adjusting for PE, low job control increased the odds of all three outcomes among both sexes, while high job demands decreased the odds of CMD among women. High job strain increased the odds of CMD and suicide attempts among men, while passive job increased the odds of all three outcomes among women. ' ' CONCLUSION ': 'The results of this study did not provide evidence for the hypothesis that psychosocial risks could be the pathways linking precarious employment with workers` mental health. Future studies in different social contexts and labour markets are needed.
Keywords: association; mediation analysis; mental health; precarious employment; precarious work; psychological work environment; psychosocial; register-based study; risk factor; Sweden